2022
DOI: 10.3390/genes13081313
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabonomic Analysis of Tamarix ramosissima Potassium (K+) Channels and Transporters in Response to NaCl Stress

Abstract: Potassium ion (K+) channels and transporters are key components of plant K+ absorption and transportation and play an important role in plant growth and development. This study revealed that K+ channels and transporters are involved in the salt tolerance molecular mechanism and metabolites of the halophyte representative plant Tamarix ramosissima (T. ramosissima) in response to NaCl stress, providing a theoretical basis for the mitigation of salt stress using halophytes. Through transcriptome sequencing and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…After liquid nitrogen treatment, according to the method of Chen et al [ 45 ], T. ramosissima root samples were subjected to 3 generations of high-throughput transcriptome sequencing. The original Illumina sequencing data were then submitted to the National Center for Biotechnology Information (NCBI) Short Reads Archive (SRA) database (SRP356215).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After liquid nitrogen treatment, according to the method of Chen et al [ 45 ], T. ramosissima root samples were subjected to 3 generations of high-throughput transcriptome sequencing. The original Illumina sequencing data were then submitted to the National Center for Biotechnology Information (NCBI) Short Reads Archive (SRA) database (SRP356215).…”
Section: Methodsmentioning
confidence: 99%
“…After treatment with liquid nitrogen, the T. ramosissima root samples were extracted and detected according to the method of Chen et al [ 45 ], and then analyzed via liquid chromatography–mass spectrometry (LC–MS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the K + accumulation level of transgenic plants under NaCl stress and ROS scavenging ability of transgenic plants was associated with improved tolerance to NaCl stress following ApKUP4 overexpression in Arabidopsis thaliana [ 39 ]. Exogenous potassium was applied to T. ramosissima roots under NaCl stress for 48 h and 168 h. In addition to helping T. ramosissima overcome oxidative damage, K + improved root K + absorption and alleviated NaCl toxicity [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a halophyte, T. ramosissima has the ability to retain more K + under salt stress conditions to adapt to different saline-alkali conditions [ 52 ]. It has been reported that the application of 10 Mm KCl under the stress of 200 mM NaCl can increase the activities of SOD, POD and CAT in leaves of T. ramosissima [ 53 ], and K + transporter, K + channel and amino acid-related genes in T. ramosissima root are up-regulated and related genes are involved in resisting NaCl stress and maintaining the growth of T. ramosissima [ 40 , 54 ]. In this study, T. ramosissima was taken as the research object, and the important metabolic pathways and key differentially expressed genes (DEGs) related to plant hormones in response to NaCl stress were excavated from the transcriptome level by exogenous potassium application.…”
Section: Introductionmentioning
confidence: 99%